Teaching Speaking Skill to The Sixth Semester Students of English Department of FKIP UKI Toraja Through English Debating - Selvi Panggua (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Indonesia Toraja, 2013)
The objective of the research is to find out whether English Debating is effective used in teaching speaking skill to the sixth semester students of English Department of FKIP UKI Toraja or not. This research used an experimental design that applied the pre-test and post-test. The population of this research was the sixth semester students of English Department of FKIP UKI Toraja, academic year 2011/2012. The number of this population was 234 students which consist of eight classes. Because the number of the population was big in number, so the writers took out 16 students as the sample of this research. The sample took randomly from all classes, and there were 2 students from each class as respondents. The result of data analysis shown that English Debating is effective used in teaching speaking skill to the sixth semester students of English Department of FKIP UKI Toraja. This believe is based on the fact that before the students taught through English Debating, their mean score was 7.6 and after giving treatment, students’ mean score was increased to 8.7, or the score was increase 1.1. Based on the result of data analysis, the writers concluded that English Debating is effective used in teaching speaking skill to the sixth semester students of English Department of FKIP UKI Toraja academic year 2011/2012